PENGARUH PENAMBAHAN PUPUK MIKRO DAN BEBERAPA GENOTIPE SORGUM (Sorghum bicolor (L.) Moench) TERHADAP INTENSITAS PENYAKIT ANTRAKNOSA (Colletotrichum sp.) DI LAHAN PETANI TANJUNG BINTANG LAMPUNG SELATAN - Farastika Unjunan Muli; Efri Efri; Muhammad Syamsoel Hadi; Radix Suharjo (Jurnal Agrotek Tropika, 2020)
One of the diseases that often found in sorghum plants is anthracnose disease caused by Colletotrichum sp. The purposed of this study was to determine the effect of adding micro fertilizer and the use of several sorghum genotypes on the intensity of anthracnose disease. The study was conducted in Sukanegara, Tanjung Bintang, South Lampung in April 2017 - February 2018 and at the Laboratory of Plant Diseases and Pests, Faculty of Agriculture, University of Lampung. The treatments were arranged using a randomized block design in a split plot design (3 times replications), the main plot was micro nutrients (with micro addition and without micro addition) and 15 subgroups of sorghum genotypes (Numbu, Samurai 1, GH3, UPCA, GH4, P / I WHP, GH6, Super 2, GH13, P / F 51-93-C, Super 1, GH5, Mandau, GH7, and Talaga Bodas). The results showed that the addition of "ZincMicro" micro fertilizers to sorghum plants did not affect the intensity of anthracnose disease, however there were differences in the intensity of anthracnose diseases between sorghum genotypes. Numbu Genotype, GH 3, and GH 13 were relatively more resistant to anthracnose disease than the other genotypes.